A programme of support for care assistants of children admitted with cerebral palsy - Lebogang L. Molefe; Leepile A. Sehularo; Magdalena P. Koen (African Journal of Disability)
Background: Cerebral palsy affects children’s movement and posture because of damage to the brain’s development. Care assistants in healthcare facilities provide care to children. Caring for the children is overwhelming, hence support is required. Such support is absent, causing frustration among care assistants, which leads to poor quality care for children.